Gedenktafeln für die Galeerensklaven des Reformierten Kollegiums Sárospatak - Pálfi, Edina (Acta Neerlandica, 2026)
Sárospatak is a prominent academic town in eastern Hungary, where three memorial plaques were unveiled between 1936 and 1939 in memory of the galley slaves. The college itself is a place of remembrance, representing 500 years of Protestant culture. There are memorial plaques here to the school’s patrons, former teachers, scholars, and the many traumas of the 20th century (World War I and II, Trianon, the Gulag camps). It is therefore surprising that, among the eight other memorial plaques located at the entrance, three plaques commemorate the galley slaves. The study explores the context of their creation, the idea, the application, and the unveiling, and interprets the phenomenon. The history of galley slavery contains not only religious but also national elements of memory, and was suitable for depicting the world of great cataclysms and tragedies in every age, as well as for analogically showing the ways of escaping from them.